Motion – Pancreatic Endoscopy is Useful for the Pain of Chronic Pancreatitis: Arguments Against the Motion - Darwin L Conwell (Canadian Journal of Gastroenterology)
Endoscopic therapy can be used to dilate strictures in the pancreatic duct, remove stones and drain pseudocysts. In addition, it provides an alternative to surgery for the management of pain in patients with chronic pancreatitis. Pain is a difficult problem in these patients, especially if substance abuse is present, and its medical management is generally unsatisfactory. The concept that pancreatic pain is related to increased pressure in the main pancreatic duct is unproven, and is not supported by the results of surgical intervention. Although pancreatic stenting is often technically successful at achieving drainage of the pancreatic duct and relieving pain over the short term, pain usually recurs with time, complications are frequent, and repeated stent changes are usually necessary. Pancreatic pseudocysts can be drained endoscopically, using transpapillary, cystogastrostomy or cystoduodenostomy approaches, but success rates are less than 50% and bleeding is a major complication. Pseudocysts should not be drained unless they are symptomatic, causing complications or enlarging. There have been no published studies comparing endoscopic with surgical or radiological modalities. Endoscopic therapy of pancreatic disorders is a new and interesting technique, but initial promising results need to be confirmed in large, well-designed clinical trials. Such studies would need to enrol large numbers of patients, and involve measurement of technical success, pain severity and quality of life parameters. At present, endoscopic techniques must be considered experimental.